Photoresponsivity and photodetectivity properties of copper complex-based photodiode - Dayan, Osman; Imer, Arife Gencer; Al-Sehemi, Abdullah G.; Ozdemir, Namik; Dere, A.; Serbetci, Z.; Yakuphanoğlu, Fahrettin (Elsevier, 2020)
Spin coated Cu(II) complex thin layer onto p-Si substrate was used in photodiode fabrication. The structural properties of novel synthesized Cu(II) complex were investigated using different techniques. The single crystal X-ray diffraction (sc-XRD) technique confirms the Cu(II) complex containing 2-mesityl1H-benzo[d]imidazole ligands and two chloride ligands have a highly distorted cis-square-planar geometry. The thermogravimetric analysis (TGA) shows that the Cu(II) complex is stable up to 248 degrees C. Also, the current-voltage measurements were performed to investigate the characteristic of photodiode based on copper complex in darkness and under solar simulator. The fundamental electrical parameters of fabricated diode were obtained using Thermionic theory and modified Norde function. The manufactured device exhibits a good response to light with the defined rise and fall time of 351 ms and 622 ms under 100 mWcm(-2) solar illumination, respectively. Furthermore, frequency dependent capacitance and conductance measurements were performed in dark and under illumination. The obtained results suggest that prepared photodiode based on Cu(II) complex could be used for organic light detection in different optoelectronic applications as photodetector, photocapacitor, and photoconductor. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Sensor; Cu complex; Optoelectronic; Photoresponse; Transient photocurrent